Ekspresi dan Pathway Analisis Gen CD14 dan IL10 pada Sapi Perah yang Terinfeksi Mastitis Subklinis - Widiono, Widiono; Gunawan, A.; Sumantri, C.; Yanthi, N. D. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2019)
Mastitis is an inflammation of  internal udder tissue caused by bacteria, it decrease milk production both in quality and quantity. This study was aimed to identify expression and pathway analysis of gene CD14 and IL10 as resistance genes in dairy infected with subclinical mastitis. Sample were taken from milk and blood 10 healthy dairy and 10 dairy containing subclinical mastitis used for CMT and RNA isolation used for gene expression analysis. The result showed that expression in healthy dairy CD14 gene had a higher expression (P<0.05). In contrast the IL10 gene had a high expression in infected dairy with subclinical mastitis (P<0.05). CD14 was an early signal receptor that activates a complex nonspecific immune response to induce various immune characteristics such as the production of inflammatory cytokines and chemokines, the production of antimicrobial peptides and so on destroy pathogens. The high expression of IL10 in infected dairy with subclinical mastitis suggested that immune responses were not functioning properly considered due to inhibiton of cytokine transduction signals by excessive production of IL10.